2020
DOI: 10.1096/fj.201902901r
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin‐1 mediates fluid shear stress‐sensitive purinergic signaling and cyst growth in polycystic kidney disease

Abstract: are contributed equally to this work.Abbreviations: Abcc6, ATP binding cassette subfamily c member 6; BB-FCF, brilliant blue-FCF; Cx30, connexin30; Cx30.3, connexin30.3; Cx37, connexin37; Entpd2, ectonucleoside triphosphate diphosphohydrolase 2; Entpd3, ectonucleoside triphosphate diphosphohydrolase 3; FBS, fetal bovine serum; FSS, fluid shear stress; Gapdh, glyceraldehyde 3-phosphate dehydrogenase; MO, translation blocking morpholino; Nt5e, ecto-5′-nucleotidase; Panx1, pannexin-1; PC1, polycystin-1; PC2, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 82 publications
1
42
0
Order By: Relevance
“…Total RNA was isolated from target cells treated with EVs using the RNeasy Mini Kit (Qiagen, Hilden, Germany). Reverse transcription and real‐time quantitative PCR were performed as previously described 39 . RPS11 was used as a reference gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from target cells treated with EVs using the RNeasy Mini Kit (Qiagen, Hilden, Germany). Reverse transcription and real‐time quantitative PCR were performed as previously described 39 . RPS11 was used as a reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription and real-time quantitative PCR were performed as previously described. 39 Potential miRNAs regulating ENTPD1 expression were identified by in silico analysis using TargetScan, 40 miRDB, 41 and microrna.org 42 databases and literature search for presence of the miRNA in the kidney, proximal tubule, HK2 cells and/or human urine. To experimentally address the involvement of miRNAs, small RNAs were isolated using the Nucleospin miRNA kit (Macherey-Nagel, Düren, Germany).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…This group also showed the contribution of P2X7 in cyst development via PANX1-dependent ATP release in ARPKD (PCK rats) [ 123 ]. Later, Verschuren et al also demonstrated the PANX1-mediated ATP release into the tubular lumen; this phenomenon was reported to be due to fluid shear stress, and established in two models of PKD: the Pkd1 knockout mice ( iKsp-Pkd1 −/− ) and Pkd1 −/− mouse distal convoluted tubule cells [ 124 ]. Moreover, they also found that PANX1 inhibition attenuated cyst growth in zebrafish PKD2 morphants.…”
Section: Regulation Of Calcium Handling In Pkd: Polycystins Cilia Calcium Channels Transporters and Purinergic Signaling-dependent Calciumentioning
confidence: 99%
“…The fluid shear stress was applied to mimic the environment of stem cells and to regulate their function and fate. [ 118,119 ] Jang et al used fluid shear stress to control the microenvironment to investigate its influence on both the fluid reabsorption of aquaporin‐2 and the orientation of actin cytoskeleton. [ 120 ] They induced this stimulus by using a syringe pump to cause the medium to flow through a PDMS‐based microfluidic system that had been integrated with a microporous polyester membrane.…”
Section: Fabrication Tools and Techniquesmentioning
confidence: 99%